Cold atmospheric plasma in orthopaedic and urologic tumor therapy - Gümbel, Denis; Daeschlein, Georg; Ekkernkamp, Axel; Kramer, Axel; Stope, Matthias B. (German Medical Science GMS Publishing House, 2017)
Cold atmospheric plasma (CAP) is a highly reactive ionized physical state thereby provoking divers biological effects. In medical applications, CAP treatment promotes wound healing, provokes immunostimulation, and is antiseptically active. Moreover, CAP interacts with antiproliferative mechanisms suggesting CAP treatment as a promising anticancer strategy. Here we review the current state of science concerning the so far investigated CAP effects on different cancer entities in orthopaedic and urologic oncology.